2012
DOI: 10.1158/1055-9965.epi-12-0740
|View full text |Cite
|
Sign up to set email alerts
|

Mental and Physical Health–Related Quality of Life among U.S. Cancer Survivors: Population Estimates from the 2010 National Health Interview Survey

Abstract: Background Despite extensive data on health-related quality of life (HRQOL) among cancer survivors, we do not yet have an estimate of the percent of survivors with poor mental and physical HRQOL compared to population norms. HRQOL population means for adult-onset cancer survivors of all ages and across the survivorship trajectory also have not been published. Methods Survivors (n=1,822) and adults with no cancer history (n=24,804) were identified from the 2010 National Health Interview Survey. The PROMIS® Gl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
247
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 323 publications
(273 citation statements)
references
References 29 publications
10
247
1
2
Order By: Relevance
“…Despite the prevalence of cancer in the elderly population and the increasing impetus for QoL measurement, not many studies have been published focusing on patient experience [26]. Weaver et al [27] showed that mental and physical health were interrelated in both young and elderly patients with cancer, which both affect their perspective about their diagnosis and expectations.…”
Section: Quality Of Lifementioning
confidence: 99%
“…Despite the prevalence of cancer in the elderly population and the increasing impetus for QoL measurement, not many studies have been published focusing on patient experience [26]. Weaver et al [27] showed that mental and physical health were interrelated in both young and elderly patients with cancer, which both affect their perspective about their diagnosis and expectations.…”
Section: Quality Of Lifementioning
confidence: 99%
“…This is important because the perception of overall quality of life implies a sense of general well-being for patients in their daily lives (Bellver, 2007). Overall quality of life is one of the main factors taken into consideration in developing and implementing effective interventions to promote wellbeing and reduce the individual and social effects of cancer (Weaver et al, 2012). As such, hypnotherapy can be considered an intervention that promotes quality of life and the perception of well-being in patients with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Given that research has shown that about one in four cancer survivors has a decreased quality of life owing to physical problems and one in 10 owing to emotional problems (142), it is clear that much more research is needed to help the growing number of cancer survivors achieve a higher quality of life. some of the 15 percent of premenopausal women diagnosed with breast cancer who have tumors that do not have hormone receptors or other molecules that can be targeted with precise therapeutics.…”
Section: Sixteen-year Childhood Cancer Survivor and Cancer Health Dismentioning
confidence: 99%